Efektivitas Model Pembelajaran Problem Based Learning(Pbl) Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Mata Pelajaran Pengantar Akuntansi Kelas Ak 1 Smk N 4 Klaten Tahun Ajaran 2016 - Sulistyarini, Oki Erfana; , Drs. Joko Suwandi, S.E., M.Pd (2017)
This study aims to describe the effectiveness of Problem Based Learning model can improve the students' critical thinking skills in the subject ofaccounting introduction class XI AK1 of SMK Negeri 4 Klaten academic year2016/2017. This is an action research (PTK ). Type of this research is qualitativedata, the data form words and sentences. The subjects of this research is thestudents of X AK1 class of SMK Negeri 4 Klaten academic year 2016/2017.Methods of data collection using observation, interviews, field notes and documentation. Each cycle consisted of four stages: lanning, action,observation, and reflection. The data analysis technique used in this researchwas descriptive comparative technique and analysis critical technique. Theresults of the research show that implementation of Problem Based Learning model can effectively improve the students' critical hinking skills in the subjectof accounting introduction class XI AK1 of SMK Negeri 4 Klaten academic year2016/2017. It wasproven, that the percentage the students' critical thinking skills before the action implementation was only 35.65%, was mproved to 57.86%after the action implementation first cycle and was increased to 83.78% after thesecond cycle action implementation.